Who moved my cheese? for teens an a-mazing way to change and win! - Johnson, Spencer (New York G.P. Putnam's Sons, 2002)
Presents the author's parable about change framed in a story about a group of high school friends trying to handle change in their lives.
Gorriceta-Rojo Family
Keywords: Change (Psychology) -- Juvenile literature; Teenagers -- Conduct of life -- Juvenile literature; Change (Psychology); Conduct of life